ASPECTS OF QUALITY OF LIFE IMPACTED ON PATIENTS WITH PROLONGED COVID-19 SYMPTOMS (LONG COVID): Aspek Kualitas Hidup yang terdampak pada Pasien dengan Gejala COVID-19 Berkepanjangan - Nanda Puspita; Honey Quentin De Queen Mcgiani (Universitas Airlangga, 2023)
Background: A subset of patients diagnosed with COVID-19 is encountering persistent post-COVID symptoms. These symptoms can significantly impede their quality of life and exert profound effects on their day-to-day functioning. Purpose: This study aimed to identify the dimensions of quality of life most affected in patients with long COVID symptoms. Methods: A cross-sectional survey was applied using the SF-36 questionnaire which was distributed on Twitter and Instagram. Furthermore, a total of 122 respondents were obtained through accidental sampling. The association between variables was analyzed using Chi-square and Mann-Whitney tests. Results: Respondents who completed the questionnaire (n=122) came from different regions, with West Java as the largest area of origin (37.70%). In addition, the majority were female (n=103, 84.4%) under 25 years old (n=92, 75.41%), and the three symptoms experienced were fatigue (n=108; 35.29%), brain fog (n=61;19.93%), and olfactory disturbances (n=54; 17.65%). There was an association between long COVID duration and gender (p= 0.03). However, there was no association between other demographic characteristics with long COVID duration (p > 0.05). General health (41.67 (IQR=29), p= 0.00) and vitality (40.00 (IQR=20), p= 0.02) were the two aspects of quality of life significantly altered in patients with long COVID symptoms more than 3 months. Conclusion: The aspects of quality of life, particularly general health and vitality, experienced a significant decline in post-COVID-19 patients with long COVID symptoms for more than 3 months.